Matematyka

Autorzy:Praca zbiorowa

Wydawnictwo:GWO

Rok wydania:2016

Oblicz a+b i a-b, wynik zapisz ... 3.92 gwiazdek na podstawie 13 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ a=3,7*10^5` 
`\ \ \ \ b=5,2*10^4`  


`ul(ul(a+b))=3,7*10^5+5,2*10^4=3,7*10^5+0,52*10*10^4=`  
`\ \ \ \ \ \ \ \ =3,7*10^5+0,52*10^5=(3,7+0,52)*10^5=ul(ul(4,22*10^5))`  

`ul(ul(a-b))=3,7*10^5-5,2*10^4=3,7*10^5-0,52*10*10^4=` 

`\ \ \ \ \ \ \ \ =3,7*10^5-0,52*10^5=(3,7-0,52)*10^5=ul(ul(3,18*10^5))`  
`ul(ul( \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 


`b) \ a=1,2*10^13` 
`\ \ \ \ b=9,8*10^12` 


`ul(ul(a+b))=1,2*10^13+9,8*10^12=1,2*10^13+0,98*10*10^12=` 
`\ \ \ \ \ \ \ \ =1,2*10^13+0,98*10^13=(1,2+0,98)*10^13=ul(ul(2,18*10^13))`  

`ul(ul(a-b))=1,2*10^13-9,8*10^12=1,2*10^13-0,98*10*10^12=` 
`\ \ \ \ \ \ \ \ =1,2*10^13-0,98*10^13=(1,2-0,98)*10^13=0,22*10^13=`  
`\ \ \ \ \ \ \ \ =2,2*10^-1*10^13=ul(ul(2,2*10^12))`    
`ul(ul( \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 


`c) \ a=7,875*10^3` 
`\ \ \ \ b=5*10^-2` 


`ul(ul(a+b))=7,875*10^3+5*10^-2=787500*10^-5*10^3+5*10^-2=`       
`\ \ \ \ \ \ \ \ =787500*10^-2+5*10^-2=(787500+5)*10^-2=787505*10^-2=`  
`\ \ \ \ \ \ \ \ =7,87505*10^5*10^-2=ul(ul(7,87505*10^3))`  

`ul(ul(a-b))=7,875*10^3-5*10^-2=787500*10^-5*10^3-5*10^-2=`      
`\ \ \ \ \ \ \ \ =787500*10^-2-5*10^-2=(787500-5)*10^-2=787495*10^-2=` 
`\ \ \ \ \ \ \ \ =7,87495*10^5*10^-2=ul(ul(7,87495*10^3))`